Challenging the misconceptions of nursing and midwifery. (2nd February 2019) - Vaughan, Paul; Carter, Elizabeth; Matthews, Bev
Abstract : Nursing has developed significantly in the NHS's 70 years. As the profession faces vacancies across its sectors, including general practice, Paul Vaughan, Elizabeth Carter andBev Matthews explore ways that we can encourage people to take up this fulfilling career